Burden of hematologic malignancies in China from 1990 to 2021: analysis from the Global Burden of Disease Study 2021 - Keding Shao; Che Wang; Weiwei Chen; Weiyao Gong; Xinci Lin; Baodong Ye; Ding Ye (BMC Public Health)
Abstract Background We aimed to provide epidemiological estimates and trend analysis based on average annual percentage change (AAPC) for age standardized rate (ASR) of hematologic malignancies in China from the Global Burden of Disease (GBD) Study 2021 to facilitate prevention strategies. Methods We estimated incidence, death, prevalence, and disability-adjusted life years (DALYs) for hematologic malignancies including leukemia, multiple myeloma (MM), non-Hodgkin lymphoma (NHL), and Hodgkin lymphoma (HL), which were defined by the International Classification of Diseases, Tenth Revision (ICD-10) in the period of 1990 to 2021 in China. Also, the relationship between sociodemographic index (SDI) and burden of hematologic malignancies was investigated by Pearson's Test. Besides, we analyzed risk factors attributed to death and disability-adjusted life-years (DALY) of hematologic malignancies. Results In 2021, there were 1,215,635 individuals suffering from hematologic malignancies across China. According to AAPC for ASRs, large increasing trends were found in incidence and prevalence due to multiple myeloma (Incidence: 4.73, 95% CI 3.97 to 5.51; Prevalence: 6.43, 95% CI 5.86 to 7.00) and non-Hodgkin lymphoma (Incidence: 1.68, 95% CI 1.35 to 2.02; Prevalence: 4.92, 95% CI 4.39 to 5.45), while significant decreasing trends in death and DALYs due to leukemia (Death: -2.03, 95% CI -2.17 to -1.89; DALYs: -2.60, 95% CI -2.88 to -2.32) and HL(Death: -4.23, 95% CI -4.34 to -4.11; DALYs: -4.48, 95% CI -4.60 to -4.37). The AAPCs of death and DALYs for hematologic malignancies in China were nearly paralleled to the globe, whereas the AAPCs of incidence and prevalence were higher than the globe, except for HL. Positive correlations between age standardized incidence and prevalence rate of hematologic malignancies except for HL and SDI were observed, while inverse correlations between age standardized death and DALY rate of hematologic malignancies and SDI were found despite NHL. Tobacco and high body mass index were the leading risk factors related to hematologic malignancies. Conclusions Despite some achievements on the burden of hematologic malignancies in China, there are still gaps with the world level. Formulation and implementation of health initiatives focusing on controlling tobacco use and high body mass index may alleviate the burden of hematologic malignancies.